Antithrombotic potential of a single‐domain antibody enhancing the activated protein C‐cofactor activity of protein S. (2nd May 2022) - Sedzro, Josepha C.; Adam, Frédéric; Auditeau, Claire; Bianchini, Elsa; De Carvalho, Allan; Peyron, Ivan; Daramé, Sadyo; Gandrille, Sophie; Thomassen, Stella; Hackeng, Tilman M.; Christophe, Olivier D.; Lenting, Peter J.; et al.
Abstract: Background: Protein S (PS) is a natural anticoagulant acting as a cofactor for activated protein C (APC) in the proteolytic inactivation of activated factors V (FVa) and VIII (FVIIIa), but also for tissue factor pathway inhibitor α (TFPIα) in the inhibition of activated factor X (FXa). Objective: For therapeutic purposes, we aimed at generating single‐domain antibodies (sdAbs) that could specifically modulate the APC‐cofactor activity of PS in vivo . Methods: A llama‐derived immune library of sdAbs was generated and screened on recombinant human PS by phage display. PS binders were tested in a global activated partial thromboplastin time (APTT)‐based APC‐cofactor activity assay. Results: A PS‐specific sdAb (PS003) was found to enhance the APC‐cofactor activity of PS in our APTT‐based assay, and this enhancing effect was greater for a bivalent form of PS003 (PS003biv). Further characterization of PS003biv demonstrated that PS003biv also enhanced the APC‐cofactor activity of PS in a tissue factor (TF)‐induced thrombin generation assay and stimulated APC in the inactivation of FVa, but not FVIIIa, in plasma‐based assays. Furthermore, PS003biv was directed against the sex hormone‐binding globulin (SHBG)‐like domain but did not inhibit the binding of PS to C4b‐binding protein (C4BP) and did not interfere with the TFPIα‐cofactor activity of PS. In mice, PS003biv exerted an antithrombotic effect in a FeCl3 ‐induced thrombosis model, while not affecting physiological hemostasis in a tail‐clip bleeding model. Discussion: Altogether, these results showed that pharmacological enhancement of the APC‐cofactor activity of PS through an original anti‐PS sdAb might constitute a promising and safe antithrombotic strategy.